TECHNOLOGY LITERACY AMONG PRIMARY SCHOOL TEACHERS FOR ENHANCING NUMERACY AND LITERACY SKILLS OF EARLY-GRADE PUPILS WITH HEARING IMPAIRMENTS IN TANZANIA - Hamadi Mtani; Shubi Kaijage; Neema Mduma (Інформаційні технології і засоби навчання)
Information Communication Technologies (ICTs) have significantly transformed the educational landscape, and offer substantial benefits for learners with special needs including those with hearing impairments. The primary purpose of this research was to determine the technological literacy level among primary school teachers in using ICTs to support literacy and numeracy skills among learners with hearing impairments and compare them based on demographic information. A quantitative analysis approach was used, involving 121 teachers from the deaf unit primary school who completed a self-rating questionnaire based on the Technology Literacy Assessment Scale developed by UNESCO. Both mean scores, the Mann-Whitney U test, and the Kruskal-Walli’s test were used to compare teachers’ technological literacy using ICTs. The results indicated that teachers' demographic information is significantly related to technological literacy at the p=0.05 level. The results found that female teachers had higher technological literacy than male teachers. Also, teachers with lower education levels were found to have higher technological literacy than those with higher levels of education. Among the teacher characteristics, working experience and age were found to have no significant difference with technology literacy as they had p-values of 0.313 and 0.212 respectively. Interestingly, teachers who specialized in special needs education were found to have higher technological literacy than those who didn’t specialize in special needs education.